(untitled) (International journal of artificial intelligence, 2025)
Listening is one of the fundamental skills required for effective communication in a foreign language. At the B1 level, learners are expected to demonstrate an intermediate command of English, which includes the ability to understand spoken language in various everyday contexts. The use of authentic materials in teaching listening has gained considerable attention among language teachers due to its potential in creating meaningful and engaging learning experiences. Authentic materials are real-life texts designed for native speakers rather than language learners, such as radio broadcasts, podcasts, interviews, video clips, TV shows, and announcements. Tailoring listening instruction around such resources can present significant benefits for B1 level students, including the development of active listening habits and increased familiarity with natural language use.